2016
DOI: 10.21831/cp.v35i3.11444
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kebutuhan Untuk Berwirausaha Pada Siswa Berkebutuhan Khusus

Abstract: Abstrak: Berwirausaha adalah salah satu alternatif masa depan bagi para penyandang kebutuhan khusus, tetapi belum banyak yang menekuninya. Penelitian ini bertujuan mengidentifikasi kebutuhan ABK untuk berwirausaha. Penelitian dilakukan melalui survei terhadap 37 siswa berkebutuhan khusus yang terdiri atas 19 laki-laki dan 18 perempuan dari 4 SLB di Yogyakarta. Sampel diambil secara purposif, yaitu mereka yang sudah berada di kelas lanjutan. Pengumpulan data menggunakan kuestioner, wawan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…Related to it, there are obstacles felt by students with special needs, which are lack of information about working field, inability to determine the decision related to job, and have not known about selfpotential. The results of this research show that students with special needs need several helps to increase their motivation and interest to be entrepreneur [8]. This research reveals the needs of students with special needs to be entrepreneur based on the level of career exploration and intensity to be entrepreneur and the obstacles felt by students with special needs.…”
Section: B Difficulties In Developing Entrepreneurship Competence Ofmentioning
confidence: 76%
See 2 more Smart Citations
“…Related to it, there are obstacles felt by students with special needs, which are lack of information about working field, inability to determine the decision related to job, and have not known about selfpotential. The results of this research show that students with special needs need several helps to increase their motivation and interest to be entrepreneur [8]. This research reveals the needs of students with special needs to be entrepreneur based on the level of career exploration and intensity to be entrepreneur and the obstacles felt by students with special needs.…”
Section: B Difficulties In Developing Entrepreneurship Competence Ofmentioning
confidence: 76%
“…Analysis results of curriculum 2013 for SMALB Tunadaksa show that basic competence related to entrepreneurship is in grade XII, so in grade X and XI, the learning is focused on the skills development. Entrepreneurship orientation towards students with physical disability needs to be taught as soon as possible in school [8]. Referring to this, the content of entrepreneurship material indirectly given in full (such as entrepreneurship training) but it is related with skills learning.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This term obviously different from an entrepreneur, although according to Kiyosaki (2001), "a successful entrepreneur generally started his career as a self-employed and that was the reason why people equalized the two of them". Another fundamental difference between an entrepreneur and self-employed is that entrepreneur has a long-term vision in forming business system that is able to continue without the presence of an entrepreneur (Purwanta, et al, 2016). In the end, researchers focus on the discussion of diffable who are conducting selfemployment.…”
Section: B Self-employedmentioning
confidence: 99%
“…Interventional approaches therefore tend to focus on students' LD-related issues to the detriment of any distinctive gifts students may have (Ruban, 2005). Johnsen and Kendrick (2005) observed that gifted students (SG) are disadvantaged if opportunities to reach their full potential are absent (Purwanta , E;Hermanto, H., Harahap , F. 2016;Wellisch & Brown, 2012). According to Dai and Chen (2013), teachers and administrators tend to place SG in a generic category.…”
Section: Introductionmentioning
confidence: 99%